Pengaruh Advertising dan Online Customer Rating Terhadap Buying Interest dan Buying Decision - Ikfran Legifen Hardi Pangestu; M. Sulhan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine and measure the effect Advertising and Online Customer Rating to Buying Interest and Buying Decision. In this study using a quantitative research approach. The population in this study are consumers who use the Tik Tok application in Pasuruan Regency. The number of samples used in the study amounted to 100 respondents. Source of data in this study using primary data obtained from distributing questionnaires to respondents. Data analysis techniques in this study using path analysis or path analysis by using software SPSS Statistics version 26, in which the data will be described, analyzed and discussed in order to prove the truth of the proposed hypothesis. The research results are as follows: (1) Advertising (X1) influential and significant to Buying Interest (Y1). (2) online customer rating (X2) there is no effect on Buying Interest (Y1). (3). Advertising (X1) influential and significant to Buying Decision (Y2). (4) online customer rating (X2) influential and significant to Buying Decision (Y2). (5).Buying Interest (Y1) positive and significant effect on Buying Decision (Y2).